2011
DOI: 10.2119/molmed.2010.00146
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aspects of Fibrin(ogen) Fragments during Inflammation

Abstract: Coagulation is fundamental for the confinement of infection and/or the inflammatory response to a limited area. Under pathological inflammatory conditions such as arthritis, multiple sclerosis or sepsis, an uncontrolled activation of the coagulation system contributes to inflammation, microvascular failure and organ dysfunction. Coagulation is initiated by the activation of thrombin, which, in turn, triggers fibrin formation by the release of fibrinopeptides. Fibrin is cleaved by plasmin, resulting in clot lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
145
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(156 citation statements)
references
References 72 publications
(60 reference statements)
2
145
0
9
Order By: Relevance
“…In the previous studies, it was shown that neither individual antioxidant levels nor total antioxidant status were significantly affected by antipsychotic treatment [25,[50][51][52]. More importantly, the altered antioxidants observed were independent of treatment since patients were antipsychotic drug-naive at entry into the study [29,50,51].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the previous studies, it was shown that neither individual antioxidant levels nor total antioxidant status were significantly affected by antipsychotic treatment [25,[50][51][52]. More importantly, the altered antioxidants observed were independent of treatment since patients were antipsychotic drug-naive at entry into the study [29,50,51].…”
Section: Discussionmentioning
confidence: 92%
“…Fibrin (ogen) has been shown to cause an inflammatory response in peripheral blood mononuclear cells induced by high levels of reactive oxygen species, increased cytokine and chemokine expression and macrophage chemoattractant protein-1 [25]. In their review, Leonard et al stated that inflammatory mediators including CRP and fibrinogen, are raised in the serum of patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, supplementary biomarkers of coagulation, that is thrombin or split products of fibrin(ogen), may be of interest to determine whether elevated D-dimer reflects increased clot formation or fibrinolysis [34].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process is closely associated with activation of the coagulation cascade. A variety of inflammatory diseases such as sepsis, rheumatoid arthritis and multiple sclerosis not only has its effects attributed to an uncontrolled inflammatory response, but also to a disturbance of coagulation [18]. Thus, when coagulation is impaired, it can contribute to the pathogenesis of many inflammatory diseases through fibrin deposition and microvascular insufficiency, as well as by enhancing the inflammatory response [33].…”
Section: Discussionmentioning
confidence: 99%
“…This is a natural response of the body to injury [17]. Fibrinolysis dissolves fibrin clot through the action of plasmin, facilitating wound healing and restoring the normal flow of blood [18].…”
Section: Introductionmentioning
confidence: 99%